1998
DOI: 10.1097/00005072-199810000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Variability of Gerstmann-Straussler-Scheinker Disease is Associated with Prion Protein Heterogeneity

Abstract: Gerstmann-Sträussler-Scheinker disease (GSS), a cerebello-pyramidal syndrome associated with dementia and caused by mutations in the prion protein gene (PRNP), is phenotypically heterogeneous. The molecular mechanisms responsible for such heterogeneity are unknown. Since we hypothesize that prion protein (PrP) heterogeneity may be associated with clinico-pathologic heterogeneity, the aim of this study was to analyze PrP in several GSS variants. Among the pathologic phenotypes of GSS, we recognize those without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
168
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 191 publications
(181 citation statements)
references
References 0 publications
11
168
0
2
Order By: Relevance
“…It is important to note that the amount of PrP sc in the patients (1 to 5) reported here is significantly smaller than that found in other GSS variants. 11,13 In agreement with the results presented here, recent studies in an Alsatian patient with GSS A117V 18 showed that the major component of amyloid fibrils was a ϳ7-kd peptide with ragged N terminus starting mainly at G 88 and G 90 . 18 The 14-and 7-kd bands, seen in GSS A117V (1 to 5), are detected by antibodies directed to the mid-region of PrP indicating that these fragments include the intact epitope recognized by mAb 3F4 consisting of residues 109 to 112.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…It is important to note that the amount of PrP sc in the patients (1 to 5) reported here is significantly smaller than that found in other GSS variants. 11,13 In agreement with the results presented here, recent studies in an Alsatian patient with GSS A117V 18 showed that the major component of amyloid fibrils was a ϳ7-kd peptide with ragged N terminus starting mainly at G 88 and G 90 . 18 The 14-and 7-kd bands, seen in GSS A117V (1 to 5), are detected by antibodies directed to the mid-region of PrP indicating that these fragments include the intact epitope recognized by mAb 3F4 consisting of residues 109 to 112.…”
Section: Discussionsupporting
confidence: 90%
“…3 GSS is caused by mutations P102L, P105L, A117V, G131V, F198S, D202N, Q212P, and Q217R in PRNP. 3,11,12 The pathological hallmark of GSS is the accumulation of PrP, with and without amyloid tinctorial properties, in the brain. 3 Our studies have shown that the pattern of PrP sc isoforms in the multiple GSS variants analyzed is different from that seen in CJD.…”
Section: Gerstmann-sträussler-scheinker Disease (Gss) Ismentioning
confidence: 99%
See 3 more Smart Citations